The Capitalization Rate of Real Estate Property in Sleman District, Yogyakarta Province, Indonesia - Panji Kusuma Prasetyanto; Hadi Sasana (Muhammadiyah University Press, 2019)
The objective of this study is to analyze the capitalization rate of luxurious houses in Sleman Regency, and its influential factors. This study will analyze the central tendency (mean) of capitalization rates for all housing areas and for each area. For the second objective, a few factors will be analyzedwhether they are statistically significant in influencing the luxurious house capitalization rates in the study areas. A few factors that will be analyzed are: the assessment of the building, lot size, location, and age of the building. This study uses cross section data only from the prime source through a stratified sampling over 5 areas of luxurious housing complexes in Sleman District: Bale Agung, Bale Hinggil, Pondok Permai Kaliurang, Hyarta and Pesona Merapi. The empirical result of this analysis shows that the mean value of the capitalization rate of luxurious houses in the study areas is. From the result of the regression analysis, it can be known which variables or factorsare statistically significant in influencing the capitalization rate of the luxurious houses in the study areas. The result shows us that the assessment of the building, lot size, location, and the age of the building are statistically significant in influencing the capitalization rates of luxurious houses in the study areas.